Faktor-faktor yang Mempengaruhi Status Gizi pada Anak Berkebutuhan Khusus - Setyaningsih, Rahayu (Jurnal Kesehatan Holistic, 2019)
The number of children with special needs in Indonesia reaches 1.6 million children. Around 115 thousand children with special needs attend school in special schools, while children with special needs who attends regular schools implementing inclusive schools number around 299 thousand. From the results of interviews with Mojosongo Surakarta Special School (SLB) teachers, it was found that there had never been a measurement of nutritional status in children with special needs in this school. The purpose is to identify the relationship between family environment factors, parental knowledge, feeding patterns and digestive disorders with nutritional status in children with special needs The subject in this study were all parents and students at the SLB Panca Bakti Mulia Mojosongo Surakarta as many as 73 people with is total sampling. Analized statistical test using chi square test, it can be obtained p: 0,003 for the relationship family environment with nutritional status, p:0,000 for the relationship between knowledge level of the parents with nutritional status, p: 0,001, for the relationship of feeding patterns with nutritional status, and p: 0,000 for the relationship between digestive disorders nutritional status. There is a significant relationship between family environment factors,parental knowledge, feeding pattern and digestive disorder with nutritional status in children with special needs.